ASPECTS REGARDING THE ORGANIZATIONAL STRUCTURE, QUALITY AND PERFORMANCE OF SPORT IN HIGHER EDUCATION IN ROMANIA - Sorin BUHAȘ; Paul Florian DRAGOȘ (Editura Universităţii din Oradea, 2017)
This study addresses sport in higher education in rel ation to its organization structure, quality and sports performance. We have studied documents, normative acts and the way in which certain decisional factors involved in higher education sports activities are organized. The lack of a concrete strategy inthis respect, renders the information sources to be relatively limited. Particularly, our research was based on scientific documentation, historical method and document analysis. There is a small number of legitimated athletes related to the number of higher education students. Higher education sport is a non-functional system, it cannot generate a representative number of participants in the National University Championships, and the international representation is not a natural consequence of the internal competition. Therefore, it is imperative for higher education sports to be the foundation of performance sports. This involves changing both the approach to this phenomenon and its organizational structure. Also, the development of human resources and sports infrastructure are essential conditions for the development ofsports activity.